Clinical ethics, information, and communication: review of 31 cases from a clinical ethics committee - Forde, R (BMJ Group, 2005)
Objectives: To summarise the types of case brought to the Clinical Ethics Committee of the National Hospital of Norway from 1996 to 2002 and to describe and discuss to what extent issues of information/communication have been involved in the ethical problems. Design: Systematic review of case reports. Findings: Of the 31 case discussions, (20 prospective, 11 retrospective), 19 cases concerned treatment of children. Twenty cases concerned ethical problems related to withholding/withdrawing of treatment. In 25 cases aspects of information/communication were involved in the ethical problem, either explicitly (n = 3) or implicitly (n = 22). Conclusion: Problems related to information/communication may underlie a classic ethical problem. Identification of these "hidden" problems may be important for the analysis, and hence, the solution to the ethical dilemma.